PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU AGRESIF SISWA DI MTS SA DARUL ISTIQOMAH - Zeti Novitasari; Ita Aristia Sa’idah; Muhammad Adib Asrori (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
This research was carried out based on the phenomenon in MTS SA Darul Istiqomah, which shows that there is aggressive behavior among students. Aggressive behavior is a form of behavior characterized by an attack to intentionally injure or bring down another person. Aggressive behavior can arise in students because of several things, one of which is parenting given by parents to children. Formulation of the problem is how the influence of parenting parents with sub-variables authoritarian parenting, democratic, permissive to aggressive behavior in students. The purpose of this study was to find out how much influence authoritarian, democratic, permissive parenting had on students' aggressive behavior. The samples used in this study were class IX students in Darul Istiqomah SA MTS as many as 25 students. The variables studied in this study are the parent parenting variable and students' aggressive behavior. Data collection is done by using questionnaires or questionnaires. Data analysis techniques used descriptive analysis techniques and multiple regression analysis techniques. The results of this multiple regression analysis are Y = 21,836 + 1,073 X1+ 0,393 X2 + 0,963 X3. The results of the analysis show that there are simultaneous contributions of 62.7%. This shows that there is a positive influence between authoritarian, democratic and permissive parenting toward partial aggressive behavior. While the sub parenting style that has the greatest influence on the emergence of aggressive behavior is authoritarian parenting.